Needs Analysis for the Development of a Children's Story Flipbook on Tugu's Traditional Pindang Serani for Elementary School Students - Manalu, Masrina Adelia; Apriliya, Seni; Lidinillah, Dindin Abdul Muiz (Indonesian Journal of Primary Education, 2024)
This study is driven by the importance of reading materials as an effort to improve students' literacy. The reading content can include knowledge of local wisdom, one example being the traditional food pindang serani from Tugu. This research aims to analyze the development needs of a children’s story flipbook, based on local wisdom, specifically focusing on pindang serani from Kampung Tugu, intended for elementary school students. The research employs a qualitative approach, with data collection techniques including interviews with a librarian representative and a class IV teacher, document excavation through the recording and analysis of available children’s storybooks containing local wisdom, and a literature review related to flipbooks about pindang serani from Tugu. The findings indicate that it is important to introduce pindang serani from Tugu to students, and that the criteria for creating the children's story flipbook include local wisdom, children’s stories, and the format of the flipbook presentation. These results serve as a foundation and reference for the development of a children’s story flipbook on pindang serani from Tugu for fourth-grade elementary students.